2020
DOI: 10.1038/s41598-020-73361-0
|View full text |Cite
|
Sign up to set email alerts
|

Offspring susceptibility to metabolic alterations due to maternal high-fat diet and the impact of inhaled ozone used as a stressor

Abstract: The influence of maternal high-fat diet (HFD) on metabolic response to ozone was examined in Long-Evans rat offspring. F0 females were fed control diet (CD; 10%kcal from fat) or HFD (60%kcal from fat) starting at post-natal day (PND) 30. Rats were bred on PND 72. Dietary regimen was maintained until PND 30 when all offspring were switched to CD. On PND 40, F1 offspring (n = 10/group/sex) were exposed to air or 0.8 ppm ozone for 5 h. Serum samples were collected for global metabolomic analysis (n = 8/group/sex)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
4
13
0
Order By: Relevance
“…These results suggest that female offspring from dams fed an HFD experienced more detrimental effects from ozone exposure than the other offspring groups. This is in accordance with our previous study [19], which found ozone-induced changes in the gut microbiome metabolites and metabolites indicative of mitochondrial stress in tissues to be more profound in these same female offspring from HFD dams than other offspring groups. For males, the ozone effects did not differ between the offspring from CD or HFD dams.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results suggest that female offspring from dams fed an HFD experienced more detrimental effects from ozone exposure than the other offspring groups. This is in accordance with our previous study [19], which found ozone-induced changes in the gut microbiome metabolites and metabolites indicative of mitochondrial stress in tissues to be more profound in these same female offspring from HFD dams than other offspring groups. For males, the ozone effects did not differ between the offspring from CD or HFD dams.…”
Section: Discussionsupporting
confidence: 93%
“…We previously showed that the perinatal HFD compared with the CD increased the body weight and fat percentage of dams throughout gestation, as well as of the offspring at postnatal day (PND) 37 [ 18 , 19 ]. Furthermore, acute ozone exposure was shown to cause pulmonary protein leakage and lung cell injury in both female and male offspring, and induced neutrophilic inflammation in female offspring [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations